The concept of organizational knowledge and its associate component parts - Ziegler, Coronda, author; Lynham, Susan A., advisor; Jennings, Louise, committee member; Doe, Susan, committee member; Folkestad, James, committee member (Colorado State University. Libraries, 2021)
Within its extant literature organizational knowledge is theorized as an entity that can be created, captured, and transferred. A pragmatic and applied definition of the concept of organizational knowledge is absent in the literature. Presumptively, the concept of organizational knowledge can be defined, clarified, and articulated, the exploratory journey of which is the goal of this dissertation. This related aim is twofold. First, to begin a process of contributing to description of the concept of organizational knowledge and its associate component parts. And, second, to inform future understanding and inquiry of the concept and its associate component parts. The dissertation presents in manuscript form, three articles that inform these two study objectives. Collectively, the three-article format begins the process of advancing a definition, description, and expanded understanding of the concept of organizational knowledge and its associate component parts. The specific research design employs three distinct lenses to this end, namely, one methodological (of methods), one conceptual (of integrative literature review) and one empirical (of case study).
Keywords: higher education; organizational knowlege; advising; qualitative analysis; literature review